Variants loci and phenotype correlation of TRIM8-related neuro-renal syndrome: three cases reports and literature review - Lv, Qiu; Niu, Yue; Xu, Zhao; Qin, Jiong; Yang, Zhixian (Frontiers in Neurology, 2024)
TRIM8-related neuro-renal syndrome (NRS), caused by pathogenic variants of the TRIM8 gene, is characterized by epilepsy, developmental delay (DD) and renal disorders. The severity of the neurological effects as well as the presence of renal disorders is variable among patients. Here, we report three additional patients with clinical features compatible with NRS, exploring clinical variability and the relationship between genotypic changes and phenotypic outcomes. Demographic and clinical data were collected from these patients. Variants were verified through triobased whole-exome sequencing or Sanger sequencing. Two de novo TRIM8 truncating variants in three NRS patients were identified in our study, including c.1327_c.1328delCCinsTG (p. Arg443*) and c.1375C ＞ T (p. Gln459*). Our three patients all exhibited drug-resistant epilepsy and early-onset DD, and two of whom developed electrical status epilepticus during sleep (ESES). Brain magnetic resonance imaging (MRI) showed periventricular leukomalacia in one patient and normal in the other two. All three patients demonstrated nephrotic range proteinuria (NRP) or nephrotic syndrome (NS) with normal renal function during follow-up. Furthermore, we reviewed published articles on TRIM8 variants and identified 9 studies. There was a total of 27 patients with TRIM8-related NRS have been identified to date. The most common clinical features are renal diseases (89%), DD (89%), followed by epilepsy (78%). 67% of patients eventually progressed to end-stage renal disease (ESRD). Focal seizure was the most frequent seizure type (57%). 52% of patients presented drug-resistant epilepsy. 64% of patients exhibited non-specific brain MRI abnormalities. Brain atrophy was the most common change (50%). Two patients with TRIM8 variants closer to the N-terminal had neurological diseases without renal damage. Five patients with TRIM8 variants closer to the C-terminal had no severe neurological diseases. Seven patients had Gln459* variant which is the most common variant (7/27, 25.9%). The severity of the renal and neurological damage of the seven patients was variable. Further research is needed to explore the relationship between genotype and phenotype of TRIM8 variants.